Cost analysis of drug treatment in hypertensive patients at social security health care family medicine units - Juan Figueroa-García; Víctor Granados-García; Ernesto Roldán-Valadez; David Rojano-Mejía; Jairo Enoc Cruz-Toledo; Silvia Palomo-Piñón (Instituto Nacional de Salud Pública, 2022)
Objective. To estimate the increase of drug treatment costs associated with predictive factors of hypertensive patients in family medicine units. Materials and methods. A generalized linear model was employed to estimate costs with data from a microcosting costing study for a 1-year time horizon. Sources of dada were medical electronic files, pharmacy records and unitary prices updated to 2019. Results. From a total of 864 patients older than 65 years were 67% and women 65%. Factors with most influence on mean drug treatment costs were diabetes, age and complications associated with hypertension. Mean annual cost of antihypertensive treatment was 61 dollars (CI95% 55,67) and median were 32 dollars (IQR 30,35) per patient. Incremental costs for diabetes were 23 dollars (CI95% 13,33) and 25 dollars (CI95% 5, 45) in the group of ≥ 65 years. Conclusion. Diabetes, age and complications were the factors with largest influence on hypertension pharmacological costs.